2016
DOI: 10.1186/s40064-016-2870-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR based genotypic characterization of pathogenic vancomycin resistant Enterococcus faecalis recovered from an Indian river along a city landscape

Abstract: BackgroundEnterococci are normal commensals of human gut, but vancomycin-resistant enterococci (VRE) are a severe threat to human health. Antimicrobial-resistant enterococci have been reported previously from Indian surface waters. However, the presence of antimicrobial resistance and virulence markers in Enterococcus faecalis, the most dominant enterococci is yet to be investigated.ObjectivesThe goal of this study was to analyse concentration of enterococci and distribution of antimicrobial resistance and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
5
15
0
Order By: Relevance
“…The measured mean concentrations (log cfu/100 mL) of E. coli (2.9-3.4) and enterococci (3.5-4.0) are comparable to other studies conducted in developing countries, for instance, in China (E. coli 1.8-3.4) (Liu et al 2009), India (enterococci 2.18-5.84) (Lata et al 2016), Southeast Asia (E. coli 2.8-4.3) (Widmer et al 2013), and Côte d'Ivoire (E. coli 2.55-3.47) (Adingra et al 2012). In the present study, 88% of E. coli and all enterococci samples exceeded bathing water quality standards (specified by USEPA), which indicates potential health risks associated with the use of the river water for domestic, bathing and irrigation purposes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The measured mean concentrations (log cfu/100 mL) of E. coli (2.9-3.4) and enterococci (3.5-4.0) are comparable to other studies conducted in developing countries, for instance, in China (E. coli 1.8-3.4) (Liu et al 2009), India (enterococci 2.18-5.84) (Lata et al 2016), Southeast Asia (E. coli 2.8-4.3) (Widmer et al 2013), and Côte d'Ivoire (E. coli 2.55-3.47) (Adingra et al 2012). In the present study, 88% of E. coli and all enterococci samples exceeded bathing water quality standards (specified by USEPA), which indicates potential health risks associated with the use of the river water for domestic, bathing and irrigation purposes.…”
Section: Discussionsupporting
confidence: 86%
“…The water quality of surface waters has been deteriorating in developing countries due to rapid industrialization and population growth (Lata et al 2016). The Betna River in southwest Bangladesh is a surface water source for about 0.1 million people living along the river.…”
Section: Introductionmentioning
confidence: 99%
“…The measured mean concentrations (log cfu/100ml) of E. coli (2.9-3.4) and enterococci (3.5-4.0) are comparable to other studies conducted in developing countries, for instance, in China (E. coli 1.8-3.4) (Liu et al, 2009), India (enterococci 2.18-5.84) (Lata et al, 2016), Southeast Asia (E. coli 2.8-4.3) (Widmer et al, 2013), and Côte d'Ivoire (E. coli 2.55-3.47) (Adingra et al, 2012). In the present study, 88% of E. coli and all enterococci samples exceeded bathing water quality standards (specified by USEPA).…”
Section: Discussionsupporting
confidence: 86%
“…The measured mean concentrations of E. coli (2.9-3.4 log cfu/100ml) and enterococci (3.5-4.0 log cfu/100ml) is comparable to few studies (Liu et al, 2009, Adingra et al, 2012, and slightly lower than few other studies (Lata et al, 2016, Widmer et al, 2013 conducted in developing countries. The measured concentrations are probably relatively low as a consequence of the tidal in and outflowing water and consequent low residence time of the bacteria.…”
Section: Spatiotemporal Variability Of Fib and Impact Of Environmentasupporting
confidence: 80%
“…Therefore, the present paper showed that the vanA gene was positive in 2 isolates (25%) of E. faecium and 9 isolates (50%) of E. faecalis by HRMA technique, also, primer specificity for vanA gene was 100.01% and melting temperature for this gene observed at 79.9 ± 0.5°C. Lata et al [21] reported a real-time PCR assay for detection of VRE with a sensitivity of 10 3 genomic equivalents. Cha et al [22] reported a multiplex real-time PCR assay Fig.…”
Section: Discussionmentioning
confidence: 99%